2013
DOI: 10.1016/j.nmd.2013.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Performance of individual items of the quantitative myasthenia gravis score

Abstract: We evaluated the quantitative myasthenia gravis score to determine which items better discriminate among patients and are most responsive to treatment. Current scoring ranges were compared to updated normative data when appropriate. Data from a previous study of intravenous immunoglobulin versus placebo in myasthenia gravis were analyzed. Each item of the quantitative myasthenia gravis score was analyzed for distribution, responsiveness and inter-item correlations. Items on swallowing, speaking and vital capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 19 publications
4
26
1
Order By: Relevance
“…We also confirmed the concordance between the QMGS and the MGFA classification of disease severity, Class I to III. It is important to acknowledge that our study group did not include patients in the MGFA Class IV and V. Barnett et al 25 similarly confirmed the sensitivity of the QMGS to differentiate disease severity among patients with MG, as well as to quantify treatment effectiveness. In particular, Barnett et al provided evidence of the discriminative value of the timed items of the QMGS, evaluating upper and lower limb function and neck endurance.…”
Section: Discussionmentioning
confidence: 62%
“…We also confirmed the concordance between the QMGS and the MGFA classification of disease severity, Class I to III. It is important to acknowledge that our study group did not include patients in the MGFA Class IV and V. Barnett et al 25 similarly confirmed the sensitivity of the QMGS to differentiate disease severity among patients with MG, as well as to quantify treatment effectiveness. In particular, Barnett et al provided evidence of the discriminative value of the timed items of the QMGS, evaluating upper and lower limb function and neck endurance.…”
Section: Discussionmentioning
confidence: 62%
“…Items were chosen based on correlations with quality of life scales and clinical change, such that some endurance items were less responsive and thus were excluded from the final measure. Endurance tests of the arms, legs and neck have been used in some measures as a marker of fatigability, demonstrating responsiveness in clinical trials [27], [28], however, they can be time consuming for routine clinical assessments. Patient reported outcomes asking specifically about impairments triggered or worsened with activity or through the day might be more feasible.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed evaluation of the ability of components of the QMGS to accurately measure MG disease activity shows that bulbar and grip strength items do not perform well, but timed items, such as limb activation, are useful [35]. Marked floor effects are observed for bulbar items, vital capacity and grip strength, a surprising result, but limiting the value of these items in the QMGS.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…The items showing most responsiveness are timed activation of upper eyelid elevation (to elicit ptosis), and timed activation of arm, leg, and neck muscles. Furthermore, new normal ranges of activation times for these items have been proposed based on updated normative data [35]. The more reliable normative ranges are 90 s for leg lift, 180 s for arm abduction, and 40 s for neck lift [35].…”
Section: Outcome Measuresmentioning
confidence: 99%
See 1 more Smart Citation